MODIFICATION OF ACTIVATED CARBON FROM SHELLS OF JENGKOL WITH TiO2 FOR PHOTODEGRADATION OF RHODAMINE B - Widya Rachmah Sari; Noor Hindryawati; R.R Dirgarini Julia Nurlianti Subagyono (JURNAL ATOMIK, 2019)
Modifying activated carbon from jengkol shells with TiO2 to degrade Rhodamine by UV irradiation has been done. Modification of KA-TiO2 photocatalyst using the impregnation method. The photodegradation test of dyes was carried out with several parameters such as the variation of KA-TiO2 catalyst weight and contact time. Photocatalyst characterization using X-ray diffraction (XRD), while for dye concentration using UV-Vis spectrophotometry. Difractogram XRD shows that the activated carbon material after modification with TiO2 metal is characterized by the emergence of typical TiO2 peaks. The results showed that the highest percentage of Rhodamine B degraded by KA-TiO2 was 94.11% with a contact time of 120 minutes and a catalyst weight of 1.5 grams.